Odobenus rosmarus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Odobenus rosmarus (Linnaeus, 1758). Syst. Nat., 10th ed., 1:38. TYPE LOCALITY: N. Atlantic. DISTRIBUTION: Arctic seas; south as far as New England (U.S.A.), Great Britain, Scandinavia, Pribilof Isis., and Honshu (Japan) at least occasionally. PROTECTED STATUS: CITES - Appendix III (Canada). ISIS NUMBER: 5301413001008001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 286, DOI: 10.5281/zenodo.7352980